Prevalence, mortality and risk factors associated with very low birth weight preterm infants: an analysis of 33 years - Julia Damiani Victora; Mariangela Freitas Silveira; Cristian Tedesco Tonial; Cesar Gomes Victora; Fernando Celso Barros; Bernardo Lessa Horta; Iná Silva dos Santos; Diego Garcia Bassani; Pedro Celiny R. Garcia; Marola Scheeren; Humberto H. Fiori; Alicia Matijasevich; et al. (Elsevier, 2020)
Objective: To assess the prevalence, mortality and risk factors associated with the birth of very low birth weight preterm infants over a period of 33 years. Methods: Four cross-sectional studies were analyzed, using data from perinatal interviews of birth cohorts in the city of Pelotas collected in 1982, 1993, 2004, and 2015. Based on perinatal questionnaires, anthropometric measurements of newborns and death certificates were analyzed to obtain the prevalence rate, neonatal mortality, and risk factors (maternal age, income and type of delivery) for very low birth weight. Results: A total of 19,625 newborns were included in the study. In the years 1982, 1993, 2004, and 2015, there were, respectively, 5909, 5232, 4226, and 4258 births. The prevalence of very low birth weight was, respectively, 1.1% (n = 64), 0.9% (n = 46), 1.4% (n = 61), and 1.3% (n = 54). There was no statistical evidence of an increasing trend over time (p = 0.11). Among the risk factors, family income in the three poorest quintiles was associated with prevalence rates that were approximately twice as high as in the richest quintile (p = 0.003). Mortality per 1000 live births for neonates weighing <1500 g decreased from 688 to 259 per thousand from 1982 to 2015 (p < 0.001), but still represented 61% of neonatal deaths in the latter year. Conclusion: Although mortality in very low birth weight decreased by more than 60% in recent years, this group still contributes with more than half of neonatal deaths. Low family income remains an important risk factor in this scenario. Resumo: Objetivo: Verificar a prevalência, mortalidade e fatores de risco associados aos nascimentos de prematuros de muito baixo peso ao nascer (MBPN) ao longo de 33 anos. Métodos: Série de quatro estudos transversais utilizando dados das entrevistas perinatais das coortes de nascimento da cidade de Pelotas coletados em 1982, 1993, 2004 e 2015. A partir de questionários perinatais, medidas antropométricas dos recém-nascidos e certidões de óbito, foram analisadas a prevalência, mortalidade neonatal e fatores de risco (idade materna, renda e tipo de parto) para prematuros de muito baixo peso ao nascer. Resultados: Foram incluídos no estudo 19.625 recém-nascidos. Em 1982, 1993, 2004 e 2015 ocorreram, respectivamente, 5.909, 5.232, 4.226 e 4.258 nascimentos. A prevalência de prematuros de muito baixo peso ao nascer naqueles anos foi, respectivamente, de 1,1% (n = 64), 0,9% (n = 46), 1,4% (n = 61) e 1,3% (n = 54). A tendência de aumento durante o período não alcançou significância estatística (p = 0,11). Entre os fatores de risco, a renda familiar nos três quintis mais pobres esteve associada a prevalências cerca de duas vezes mais altas do que no quintil mais rico (p = 0,003). A mortalidade por 1.000 nascidos vivos para os neonatos com peso < 1500 g caiu de 688 para 259 por mil ao longo dos anos (p < 0,001), mas ainda representa 61% dos óbitos neonatais em 2015. Conclusão: Embora a mortalidade nos prematuros de muito baixo peso ao nascer tenha diminuído em mais de 60% nos últimos anos, esse grupo ainda contribui com mais da metade dos óbitos neonatais. A baixa renda familiar continua a ser fator de risco importante nesse cenário.